Language and cognitive communication disorder during post-traumatic amnesia: Profiles of recovery after TBI from three cases. (6th December 2017) - Steel, Joanne; Ferguson, Alison; Spencer, Elizabeth; Togher, Leanne
ABSTRACT: Background : There has been limited empirical speech–language pathology (SLP) study of language and cognitive communication during post-traumatic amnesia (PTA) and the early stages after TBI. The purpose of the current research was to explore the potential means and utility of assessing cognitive communication during PTA and the post-acute recovery period. Method : This research used a longitudinal mixed methods design to describe language and cognitive communication assessment and recovery profiles of three patients with TBI. Cognitive communication was assessed with repeated standardised and non-standardised methods during PTA (rated with Westmead PTA Scale) and at follow-up 3 months after PTA emergence. Results : All participants demonstrated a profile of language and cognitive communication strengths and weaknesses during PTA and the post-acute period, also evident at follow-up. Improvement occurred gradually throughout PTA, although with individual fluctuation across test occasions. There was no marked change in communication function immediately before and after PTA emergence, indicating that cognitive communication ability and those functions measured on the Westmead PTA Scale (memory and orientation) did not recover at the same rate. Conclusion : It was feasible to assess language and cognitive communication throughout PTA and the post-acute period, and early assessment results were relevant to the patient's ongoing communicative function. It is suggested that early and repeated SLP assessment may contribute to the prediction of persisting cognitive communication issues.